2015
DOI: 10.17265/2161-6221/2015.3-4.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between Conventional and Microwave-Assisted Extraction of Natural Colorant From Mesocarp and Exocarp of Cocus Nucifera

Abstract: This study aimed at exploring the feasibility of using the mesocarp and exocarp of Cocus nucifera as a natural colorant using microwave-assisted extraction in which often regarded as a waste materials. The effects of microwave power and heating time on the yield of colorant, pH and colour determination were investigated. The highest colorant yield in mesocarp and exocarp was found to be 6.0% (8 min of extraction at 100 W) and 6.8% (12 min of extraction at 300W), respectively. While the control, extraction of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…About 10 g of each mesocarp and exocarp samples were transferred into a conical flask containing 200 ml of 0.1 M sodium hydroxide (ratio of 1:20). The mixtures were then heated in a microwave (Samsung, Korea) at 300W for 2 minutes [15]. After microwave heating, the mixtures were allowed to be cooled to room temperature before filtered using filter paper (150 mm) (CHM, Germany).…”
Section: Methods Of Extractionmentioning
confidence: 99%
“…About 10 g of each mesocarp and exocarp samples were transferred into a conical flask containing 200 ml of 0.1 M sodium hydroxide (ratio of 1:20). The mixtures were then heated in a microwave (Samsung, Korea) at 300W for 2 minutes [15]. After microwave heating, the mixtures were allowed to be cooled to room temperature before filtered using filter paper (150 mm) (CHM, Germany).…”
Section: Methods Of Extractionmentioning
confidence: 99%
“…Also, among all the samples studied, the combination of mesocarp and exocarp resulted in the highest values of TPC (1.73±1.99 mg GAE/g; p<0.05), TFC (2.24±0.04 mg QE/g; p<0.05) and TTC (0.23±0.01 mg TE/g) and they were significantly different from every other sample (Figure 2). In a study conducted by Rodiah et al (2018) which assessed the polyphenolic contents of mesocarp and endocarp of coconuts, the authors found that the mesocarp had a TPC value (32.24 mg GAE/g) and it was significantly higher than the TPC value of the exocarp (8.63 mg GAE/g). However, the authors did not assess the TPC values of the combination of mesocarp and exocarp.…”
Section: Physicochemical and Phytochemical Properties Of Different Pa...mentioning
confidence: 99%
“…The coconut husk consists of the endocarp, mesocarp, and exocarp which make up about 30-35% of the whole coconut (Tan et al, 2007). It is estimated that 5280 kg of dry coconut husk is produced per hectare every year which is significant and (Rodiah et al, 2018) there is a dire need to find a way to manage the waste. One approach is to add value to the waste by utilizing the coconut husk as a natural dye.…”
Section: Introductionmentioning
confidence: 99%